Characteristics of Density and Hardness on Caloric Value of Substitution of Biomass and Pet Plastics as Refused Derived Fuel Pellets - Pratiwi Claudia Gaina; Mega Mutiara Sari; I Wayan Koko Suryawan; Wisnu Prayogo; Kuntum Khoiro Ummatin; Qurrotin Ayunina Maulida Okta Arifianti; Niswatun Faria (Universitas Negeri Semarang, 2023)
The utilization of biomass and polyethylene terephthalate (PET) waste as raw material for refuse-derived fuel (RDF) has been studied. However, physical such as density and hardness are still not widely used. This study aimed to determine the relationship between variations in the composition of PET and physical garden waste density and hardness on the quality of the caloric value of RDF. Density measurements were carried out with the Ultrapyc 1200e instrument. While for hardness, using the Shore D method. The Shore D Hardness test is a standardized test that involves evaluating the amount of depth that may be penetrated by a certain indentation. The lowest density is RDF pellets for food waste at 1,537 kg/m3 and consists of RDF pellets for plastic waste at 2,560 kg/m3. In line with the density, the hardness value increases with the addition of the PET composition. The density and hardness values in the RDF mixture show a simultaneous relationship to the heating value. The highest caloric value achieved is the use of 100% PET as pellets which can reach 5765 kcal/kg.